Desain Lean Production Dengan Aspek Sustainability dan Logika Fuzzy pada Value Stream Analysis Tools - Famila Dwi Winati; Adhe Rizky Anugerah; Dwi Adi Purnama (Jurnal Ilmiah Teknik Industri, 2017)
This article measures and identifies waste and designs alternatives to reduce waste in one SME in Yogyakarta, thus increasing efficiency. The lean manufacturing approach uses Value Stream Mapping that applies sustainability concepts. The research methodology used in this research is case study strategy. Based on the analysis of Current State Mapping there are many activities that are not important and should be reduced. The sustainability aspect in Gendhis Bag covers the environmental aspect with a 10% limit on skin waste and 15% for PVC waste. Energy consumption for production is 750 watts and labor cost is Rp 32,800 per unit. Safety operators have a very small accident rate, while the largest Physical Load Index score is in the cutting department. Future state VSM shows that NNVA and NVA time can be significantly reduced and lead time can be reduced, so production can increase 12 units per day.